2021
DOI: 10.1017/s0022215121002309
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-orbital-cerebral mucormycosis: fungal epidemic in a viral pandemic

Abstract: Background Treatment of coronavirus disease 2019 infection can result in immunosuppression. Rhino-orbital-cerebral mucormycosis is a frequent co-infection, even after recovery. Methods An ambispective interventional study was conducted of 41 coronavirus patients with rhino-orbital-cerebral mucormycosis at a tertiary care centre from March to May 2021. Results There were 28 males and 13 females with a mean age of 48.2 years (range, 21–68 years). Twelve had long-standing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Chouhan et al in their research found 41 patients who satisfied the diagnostic criteria of CAROCM and accordingly, had a male preponderance (n=28), 36 patients had a history of steroid use, 40 patients were diabetics and majority of them had received oxygen while in the hospital. [18] The current study had a similar male preponderance. (88.33%) Two systematic reviews conducted in the past on CAROCM have identified diabetes mellitus as the most common comorbidity followed by hypertension.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Chouhan et al in their research found 41 patients who satisfied the diagnostic criteria of CAROCM and accordingly, had a male preponderance (n=28), 36 patients had a history of steroid use, 40 patients were diabetics and majority of them had received oxygen while in the hospital. [18] The current study had a similar male preponderance. (88.33%) Two systematic reviews conducted in the past on CAROCM have identified diabetes mellitus as the most common comorbidity followed by hypertension.…”
Section: Discussionsupporting
confidence: 61%
“…Certain predisposing factors identified for CAROCM include uncontrolled diabetes mellitus, use of systemic corticosteroids, prophylactic broad-spectrum antibiotics that disrupt the nasal commensals enabling invasion of pathogenic fungi, immune-suppressive medications and diseases, organ transplant and hematological malignancies. [2] , [9] , [10] , [18] Interestingly, inhalation of steam, which was widely advised my many practitioners in India to relieve nasal congestion in COVID, was found to damage the delicate nasal mucosa facilitating mucorale invasion. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Scant literature is available including case reports, small data-based case series, and reviews describing an association between COVID-19 and ROCM [ Table 3 ]. [ 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 ] However, the swiftness and ferocity with which this pandemic has engulfed the world and the unprecedented investment of healthcare professionals and resources has made it necessary to evaluate any level of evidence available in the literature not only to guide management strategy but also to plan current and future research. With varied clinical forms of mucormycosis, pulmonary mucormycosis was the predominant clinical form (87.5%) observed, while ROCM was the most common presentation (28.6%) that was noted in developing countries like India.…”
Section: Rocm and Covid-19 Disease: Perspectives And Changing Trendsmentioning
confidence: 99%
“…The frequency of cerebral involvement in Covid-19-associated rhino-orbito-cerebral mucormycosis was reported to be 22 per cent. 34,35 The pooled prevalence of intracranial involvement was 13 per cent in the current study.…”
Section: Discussionmentioning
confidence: 41%